Inovasi Pupuk Organik Cair Kulit Pisang Mengandung Trichoderma sp. untuk Meningkatkan Ketahanan Tanaman Cabai Rawit Hiyung di Desa Sungai Hanyar - Maimunah, Maimunah; Miladiarsi, Miladiarsi; Jannah, Fathul; Zaki, Muhammad; Yulianti, Evi; Rahimah, Ainor; Fatimah, Maulina; Raihanah, Siti; Ikhsan, Maulana; Nuraini, Siti; Sofiya, Nur Ainin; Apriliadi, Muhammad Akbar; Putri, Natasya Amalia; A'isy, Muhammad Fauzan; Mutmainah, Iis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Hiyung chili is a horticultural commodity with high economic value, but its productivity still fluctuates due to cultivation constraints and dependence on synthetic chemical fertilizers. This activity aims to increase farmer capacity and plant growth of Hiyung chili through the application of liquid organic fertilizer (LOF) based on banana peel waste enriched with Trichoderma sp. The activity was carried out in Sungai Hanyar Village using a Participatory Action Research (PAR) approach through socialization, training, practice, and field mentoring. Evaluation was carried out using pre-test and post-test methods to measure changes in knowledge, attitudes, and skills of participants. The results showed an increase in farmer capacity from 50% to 84.67% after the activity. Improvements occurred in the understanding of LOF, acceptance of organic fertilizer technology, and technical skills in its manufacture. The application of LOF also showed better plant growth compared to the control. The use of banana peel waste as LOF has the potential to be an environmentally friendly and sustainable fertilizer alternative.